Church as community : theological foundations and development in practice - Codd, Anne Marie (Trinity College (Dublin, Ireland). Department of Hebrew, Biblical and Theological Studies, 2000)
Since human beings are historical in nature it follows that the church, as a community, exists in time and place. Part I of the dissertation identifies a tradition, time and place in relation to which this study of church as community will be done. It is a historical and sociological exploration of the Roman Catholic Church in the Republic of Ireland, 2000 years or so after Christ. Since the 1960s this Church has been characterised by rapid and extensive change which illustrates the interrelatedness of the self-understanding of religious believers and their socio-historical contexts. Trajectories of the changes in Irish society and in the Roman Catholic Church in Ireland are traced. Theoretical perspectives are taken through a discussion of the sociology of religion in Irish society. Patterns of religious belief and practice are studied against a background of economic development, and social and cultural transformations. The vast majority of the population of Ireland are affiliated to the Roman Catholic Church, and until the 1960s their allegiance was largely unquestioned. From the research reviewed here it emerges that they still profess high levels of religious faith. At the same time, they show a decreasing commitment to Church attendance and a growing autonomy in relation to Church authority. Irish society is characterised by progress combined with a significant degree of polarisation. The question follows: How is the Roman Catholic Church in Ireland to understand itself in this context? How, in particular, is the parish community, where Church is most immediately and concretely realisable, to structure its life and fulfil its mission.
Keywords: Hebrew Biblical and Theological Studies, Ph.D.; Ph.D. Trinity College Dublin